Evaluation of the Polish opinion-giving model applied by court experts specialising in examination of written documents : tendencies for changes - Zieniewicz, Iwona (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The publication will present the most important problems related to the model of experts in the field of examination of written documents, which functions in Poland, with particular emphasis on the experts registered on court lists. These lists should be a reliable — and thus helpful — source for the search for and selection of the best expert in a given case. However, they do not serve this function properly. The very level of opinions drafted by experts in the field of handwriting analysis is also an extensively discussed issue. The reasons for this status quo should be perceived, inter alia, in the lack of uniform procedures for carrying out analyses and formulating conclusions in the field of handwriting documents examination, as well as in the lack of a reliable and comprehensive training system for experts in this field of knowledge.
Keywords: expert; documents expert examination; expert opinion; documents examination; handwriting analysis